The novel Tenzing 7 delivery catheter designed to deliver intermediate catheters to the face of embolus without crossing: clinical performance predicted in anatomically challenging model - Frölich, Andreas M. J.; Kim, Warren; Stribrny, Knut; Jansen, Olav; Möhlenbruch, Markus Alfred; Szikora, Istvan; Wodarg, Fritz; Fiehler, Jens; Otto, Kim; Chou, Tony; Buhk, Jan Hendrik; English, Joey (Journal of neuroInterventional surgery, 2021)
Background In large vessel occlusionstroke, navigation of aspiration catheters (AC) can be impeded by vessel tortuosity and the ophthalmic artery origin. A novel tapered delivery catheter was designed to facilitate delivery without disturbing the embolus. We assessed AC deliverability in vitro and validated the observations in a first-in-human experience. Methods In a vascular model with three challenging craniocervical scenarios, two commercial AC were advanced from the carotid to the middle cerebral artery by four neurointerventionalists. Catheter deliverability with standard microwire and microcatheter (MC) combinations and the Tenzing 7 (T7) Delivery Catheter (Route 92 Medical, San Mateo, CA) were compared. Operators rated aspects of catheter deliverability on a 5-point scale. Results were compared with device delivery patterns at a neurovascular center before and after clinical introduction of T7. Results In vitro, success rate and speed were higher with T7 (96%; mean 30±10 s) than with MC (65%; 72±47 s, p<0.001 each), with fewer interactions with the occlusion site (T7: 54% vs MC: 77%, p=0.004). T7 received superior ratings regarding carotid artery deflection (T7: 2, IQR1-3 vs MC: 3, IQR2-3, p<0.001), guide catheter pushback (T7: 2, IQR1-3 vs MC: 3, IQR3-3, p<0.001) and ophthalmic artery passage (T7: 1.5, IQR1-2 vs MC: 4, IQR3-5, p<0.001). Before introduction of T7 at a single center, delivery of AC to a large vessel occlusion without crossing was achieved in 15/123 cases (12%). With T7, this rate was 28/31 patients (90.3%). Conclusion Compared with microcatheter and microwire combinations, T7 improves aspiration catheter delivery in vitro, minimizing the need to cross the occlusion. Initial clinical experience appears to validate the model’s observations.
Gesehen am 20.10.2021